2014
DOI: 10.1007/978-3-319-07980-6_10
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Comparison Between Presuppositions and Indirect Scalar Implicatures

Abstract: We compare two aspects of meaning, namely the presupposition of stop in the scope of negation (John didn't stop going to the movies on Wednesday., → John used to go to the movies before Wednesday.) and scalar implicatures associated with strong scalar items under negation (John didn't always go to the movie last week. → John sometimes went to the movies last week.) ('Indirect Scalar Implicatures' (ISIs) Chierchia, 2004). Our results replicate the finding by Chemla and Bott (2013) that global presupposition int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 36 publications
9
48
0
Order By: Relevance
“…The child data from Experiment 2 suggest that the UNIVERSAL reading arises from the basic projection mechanism, with the EXISTENTIAL reading being derived through some additional mechanism such as domain restriction. Reaction time data from adults reveal a delay associated with the PRESUPPOSI-TIONLESS reading, suggesting that it involves an additional costly mechanism (e.g., local accommodation), in line with previous results in the literature (Chemla & Bott 2013;Romoli & Schwarz 2014). In addition, the child data, combined with previous results from Bill et al (2016), suggest that in the case of negative quantifiers, there may be two routes for arriving at the PRESUPPOSITIONLESS reading.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The child data from Experiment 2 suggest that the UNIVERSAL reading arises from the basic projection mechanism, with the EXISTENTIAL reading being derived through some additional mechanism such as domain restriction. Reaction time data from adults reveal a delay associated with the PRESUPPOSI-TIONLESS reading, suggesting that it involves an additional costly mechanism (e.g., local accommodation), in line with previous results in the literature (Chemla & Bott 2013;Romoli & Schwarz 2014). In addition, the child data, combined with previous results from Bill et al (2016), suggest that in the case of negative quantifiers, there may be two routes for arriving at the PRESUPPOSITIONLESS reading.…”
Section: Discussionsupporting
confidence: 87%
“…One way to interpret this, which speaks to our third research question, is that the observed slow-down is indicative of an additional step that is required in order to access the PRESUPPOSITIONLESS reading. Such an interpretation is in line with previous results in the literature (Chemla & Bott 2013;Romoli & Schwarz 2014), and is compatible with all theories positing an extra mechanism responsible for suspension.…”
Section: Truecontrolsupporting
confidence: 92%
See 1 more Smart Citation
“…As we will see, the results of our Experiment 1 run counter to this expectation. Regarding the processing of implicatures, we will merely note here that the majority of previous experimental work suggests that interpreting a sentence without its implicatures is equivalent to not deriving the implicatures rather than cancelling them; for instance, Bott & Noveck (2004) and Bott et al (2012) provide evidence that participants who give implicature-less responses are faster to respond than those who give implicature-based responses, and Cremers & Chemla (2014) report similar results for indirect scalar implicatures, which are the kind that concern us here (though see also Romoli and Schwarz 2015).…”
Section: Negative Polarity Items and Intervention Effectsmentioning
confidence: 54%
“… Cremers and Chemla () and Romoli and Schwarz () present evidence that indirect SIs are not costly, but Cremers and Chemla () argue that there are confounds in these findings, and they show that once these confounds are overcome, the computation of indirect SIs does come with a processing delay.…”
mentioning
confidence: 99%